Anatomoradiographic description of the teeth of pacas bred in captivity (Agouti paca, Linnaeus, 1766) - Oliveira, F. S.; Canola, J. C.; Oliveira, P. T.; Pecora, J. D.; Capelli, A. (Blackwell Publishing, 2006)
Two newborn males, two adult males 9 and 72 months old, one newborn female and two adult females of 30 and 54 months old pacas were used. Animals were radiographed on lateral recumbency, teeth were extracted and the vestibulolingual and mesiodistal lengths were achieved at the occlusal surface, besides the longitudinal length. The lower incisors presented greater length in relation to the other ones and sinuous shape; the upper incisors, relatively smaller, are practically straight. There is no canine tooth, and after a great diastema there is one premolar and three molars in each hemiarcade. In adult pacas, the enamel of incisors presents yellowish colour, mainly in the labial surface; in the premolars and molars, the enamel is present as internal sheets disposed nearly in a parallel way and in vestibulolingual direction, through practically all the dental length, which provides several joined teeth aspect.